ANALISIS PELAKSANAAN RUJUKAN RAWAT JALAN TINGKAT PERTAMA PADA PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN (Studi Kasus di Puskesmas Neglasari Kota Tangerang) - Firdiah, Mutia Rizqa; Sriatmi, Ayun; Fatmasari, Eka Yunila (Jurnal Kesehatan Masyarakat (Undip), 2017)
The high ratio of refeffals at the Public Health Center of Neglasari is 23,43% which exceeds the standard more than 5%. The results of the preliminary study indicate that the referral in the Neglasari Community Health Center is due to the condition of the patient who is required to be referred, the absence of a change in the condition of the patient causing the patient to be referred, the incomplete medication, the limited health equipment facility in the health services for the BPJS Health participants. The purpose of this study was to analyze the implementation of first referral to BPJS Health participants at Neglasari Public Health Center Tangerang City. This research includes descriptive research using qualitative method. The results showed that most diseases that had to be referred are hypertension, diabetes melitus, heart disease, and leprosy. The availability of doctors is not sufficient if seen from the ratio of the number of doctors to the number of registered participants. The availability of drugs is broadly available, but there are still some drugs that are inadequate supplies such as sugar remedies, heart medicine, high blood pressure medicine, and painkillers. Completeness of health equipment facilities is not yet complete. The doctor’s understanding as a gatekeeper is good. If a patient asks for referral, but if the patient still wants to be referred, the doctor will add “On Request” notes In the referral letter. Suggestion from this research is hopefully Public Health Center of Neglasari can improve health service quality to patient especially BPJS Health patient with addition of health equipment facility. In addition, Puskesmas Neglasari is also expected to assist BPJS Health in socializing the First Outpatient Referral Regulation (RJTP) regulation in accordance with prevailing regulations in BPJS Health. And for the BPJS Health is to review the contents of the credential form on the part of health equipment facilities, and reprogram the primary-care application so that doctors can refer patients appropriately.